Rehabilitation Exoskeletons: a Systematic Literature Review - Rivera Robles, Jonatan; Bory Reyes, Juan; Hernández Simón , Luis Manuel; Palacios Hernández, Jesús Ignacio Eduardo (Revista Mexicana de Ingenieria Biomedica, 2024)
The accelerated evolution of technology in the last decade has enabled breakthroughs in fields of science such as medicine, robotics, bionics and rehabilitation by integrating knowledge and techniques from these areas. Rehabilitation exoskeletons are examples of multidisciplinary integration in the development of physiotherapeutic intervention tools that have shown significant results in patients with neurological diseases. This systematic literature review presents the advances, developments and characteristics of these devices and their current situation, specifically those that have the greatest impact on their co-citation and co-occurrence so that the works integrated into the research are verifiable and reliable. This is done through the implementation of a methodology for the elaboration of the state of the art on the subject of rehabilitation exoskeletons, based on the implementation of scientific databases, systematised digital bibliometric tools and their systemic integration. The scientific literature on rehabilitation exoskeletons was compiled from papers published between January 2014 and 30 November 2023, which were retrieved from the Web of Science. The first stage was to define the inclusion and exclusion criteria in order to limit the search within the scientific database, and the second stage was to process the information and works obtained in order to process them using the CiteSpace software, as a result of this stage, the co-occurrence analysis was obtained, a graphical network was generated and a co-citation analysis, subsequently with the data obtained from the previous stages, the PRISMA method was implemented. As a third step, the results obtained from the 1511 publications and 108,512 reference citations dealing with rehabilitation exoskeletons are presented. A discussion of the main characteristics, advances, limitations, challenges and trends of these devices is presented.